Unified and Benign Synthesis of Spirooxindoles via Bifunctional and Recyclable Iodide‐Salt‐Catalyzed Oxidative Coupling in Water. Issue 35 (5th September 2019) - Wang, Dangui; Lu, Xunbo; Sun, Shaohan; Yu, Huaibin; Su, Huimin; Wu, Yuzhou; Zhong, Fangrui
Abstract : Herein we develop a novel micellar catalytic system based on amphiphilic bifunctional iodide salts for oxidative intramolecular α‐oxygenation and α‐amination of carbonyl substrates in water, thus enabling a unified and benign synthesis of various 2‐oxindoles containing spirotetrahydrobenzofurans, spiroisochromanones, spiroindolines and spirolactones. Notably, the terminal oxidant H2 O2 produced water as the only by‐product. The excellent recyclability of the aqueous medium containing the catalyst further highlights the synthetic utility of this system. Abstract : A micellar catalytic system based on amphiphilic bifunctional iodide salts is developed for oxidative α‐functionalization carbonyl substrates in water, enabling unified and benign synthesis of various 2‐oxindoles containing spirotetrahydrobenzofurans, spiroisochromanones, spiroindolines and spirolactones.